Brighter by the day : [large type] waking up to new hopes and dreams - Roberts, Robin, 1960-; Burford, Michelle (Grand Central Publishing Large Print, 2022)
"Drawing on advice and knowledge she gleaned from conversations with loved ones, spiritual practices, and life experiences, Robin offers a window into how she feeds her own mind, spirit, and soul and invites readers to do the same. With a deeply personal touch, she explains that just like any skill, optimism requires practice and demonstrates how we can shift our mindsets and give ourselves permission to let our best intentions take root and be true."--Publisher